Tripterygium Glycosides Tablet Ameliorates Renal Tubulointerstitial Fibrosis via the Toll-Like Receptor 4/Nuclear Factor Kappa B Signaling Pathway in High-Fat Diet Fed and Streptozotocin-Induced Diabetic Rats - Ze-jun Ma; Xiao-na Zhang; Li Li; Wei Yang; Shan-shan Wang; Xin Guo; Pei Sun; Li-ming Chen (Journal of Diabetes Research)
Tripterygium glycosides tablet (TGT) is a Chinese traditional medicine that has been shown to protect podocytes from injury and reduce the proteinuria. The aim of this study was to assess the effect of TGT on renal tubulointerstitial fibrosis and its potential mechanism in high-fat diet fed and STZ-induced diabetic rats. Rats were randomly divided into normal control rats (NC group), diabetic rats without drug treatment (DM group), and diabetic rats treated with TGT (1, 3, or 6 mg/kg/day, respectively) for 8 weeks. The results showed that 24 h proteinuria and urinary N-acetyl-glucosaminidase (NAG) in diabetic rats were decreased by TGT treatment without affecting blood glucose. Masson’s trichrome stains showed that apparent renal tubulointerstitial fibrosis was found in DM group, which was ameliorated by TGT treatment. The expression of α-SMA was significantly decreased, accompanied by increased expression of E-cadherin in TGT-treated rats, but not in untreated DM rats. Further studies showed that TGT administration markedly reduced expression of TLR4, NF-κB, IL-1β, and MCP-1 in TGT-treated diabetic rats. These results showed that TGT could ameliorate renal tubulointerstitial fibrosis, the mechanism which may be at least partly associated with the amelioration of EMT through suppression of the TLR4/NF-κB pathway.